Des friches et des ruines - Danièle Méaux (IdeAs)
The decline of industrial activity has led to many important infrastructures falling into disuse, structures often situated in urban centers, with the presence of these abandoned sites posing problems for both town-dwellers and local authorities. While they highlight an economic crisis with serious social repercussions, they also attract film-makers or photographers who like to display the ruins, aestheticising the fragmented forms and tatty textures. Certain of them even seem to cultivate a kind of attraction in the portrayal of catastrophes. Such are the inclinations of two French photographers, Yves Marchand and Romain Meffre, whose work devoted to the city of Detroit is renowned. Far from the work of the latter we find the photographic series produced by Joel Sternfeld on the High Line in New York, between April 2000 and July 2001. The American photographer, known for his work in colour on landscapes, took a series of shots of an abandoned elevated railway line. While the work of Yves Marchand and Romain Meffre provokes a certain astonishment on the part of the observer (who becomes almost a voyeur), the shots of Joel Sternfeld allow the spectator to share the experience of his strolls along the line. What emerges in these images is the vitality and diversity of the vegetation, changing with the seasons. The book, published in 2001, relates to the gesture of appropriation which the walk inspires, presaging the future destiny of the site. The photographer is actually campaigning for the preservation of the High Line and its conversion to a walkway.